Pro Spring Security - Scarioni, Carlo (Apress : Imprint: Apress, 2013)
Security is a key element in the development of any non-trivial application. The Spring Security Framework provides a comprehensive set of functionalities to implement industry-standard authentication and authorization mechanisms for Java applications. Pro Spring Security will be a reference and advanced tutorial that will do the following: Guides you through the implementation of the security features for a Java web application by presenting consistent examples built from the ground-up. Demonstrates the different authentication and authorization methods to secure enterprise-level applications by using the Spring Security Framework. Provides you with a broader look into Spring security by including up-to-date use cases such as building a security layer for RESTful web services and Grails applications.